Implementation of an Automatic Defacement Detection System on Government Websites Using N8N - Faisal Anwar; Apriade Voutama (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2026)
Advances in information technology have encouraged the use of websites as a means of public services in various sectors. One sector that utilizes websites to support its services is the government sector. However, in its implementation, this system faces cybersecurity challenges, namely defacement attacks, which involve unauthorized changes to the appearance or content of a website that are often detected too late and can erode public trust. This research aims to develop a system capable of detecting indications of defacement attacks automatically and more quickly. The method applied in this research is a system experiment approach, which utilizes the n8n workflow automation platform, operated on a scheduled basis via schedule triggers. This system is tasked with monitoring website domains by applying analytical techniques based on keyword matching to page content that is potentially subject to change. The monitoring data is then processed using a function node to match specific keywords, such as "judol," "bokep," "gacor," and "slot," which frequently appear in defacement cases. Once keywords are detected, the system then sends a warning message to the administrator via Discord. The results show that the system is capable of automatically detecting keyword occurrences and sending a warning message via Discord webhook to the administrator when a change in website content is identified. This system also helps speed up the verification process by providing direct links to related pages so that handling can be done more quickly and effectively.